Baicalin Rescues Cognitive Dysfunction, Mitigates Neurodegeneration, and Exerts Anti-Epileptic Effects Through Activating TLR4/MYD88/Caspase-3 Pathway in Rats - Yang J; Jia Z; Xiao Z; Zhao J; Lu Y; Chu L; Shao H; Pei L; Zhang S; Chen Y (Dove Medical Press, 2021)
Jiali Yang,1,* Zhixia Jia,1,* Zhigang Xiao,1 Jing Zhao,2 Ye Lu,2 Li Chu,3 Hui Shao,1,2 Lin Pei,1,2 Shaodan Zhang,4 Yuan Chen4 1School of Integrated Traditional Chinese and Western Medicine, Hebei University of Chinese Medicine, Shijiazhuang, Hebei, 050200, People's Republic of China; 2Hebei Key Laboratory of Turbidity, Hebei Academy of Chinese Medicine Sciences, Shijiazhuang, Hebei, 050011, People's Republic of China; 3School of Pharmacy, Hebei University of Chinese Medicine, Shijiazhuang, Hebei, 050200, People's Republic of China; 4Pediatrics, The Second Hospital of Hebei Medical University, Shijiazhuang, Hebei, 050051, People's Republic of China*These authors contributed equally to this workCorrespondence: Shaodan Zhang; Lin PeiPaediatrics, The Second Hospital of Hebei Medical University, Shijiazhuang, Hebei, 050051, People's Republic of ChinaTel/Fax +86 13653115066; +86 13831190309Email 13653115066@163.com; peilin13831190309@126.comPurpose: This study aims to evaluate the beneficial effects of anti-epileptic mechanisms of baicalin (BA) on cognitive dysfunction and neurodegeneration in pentylenetetrazol (PTZ)-induced epileptic rats.Methods: First, PTZ-induced epileptic rats were administered intraperitoneally a sub-convulsive dose of PTZ (40 mg/kg) daily, and the seizure susceptibility (the degree of seizures and latency) was evaluated using Racine's criterion. Then, classical behavioral experiments were performed to test whether BA ameliorated cognitive dysfunction. Neurodegeneration was assessed using Fluoro Jade-B (FJB), and NeuN staining was used to determine whether BA offered a neuroprotective role. After BA had been proven to possess anti-epileptic effects, its possible mechanisms were analyzed through network pharmacology. Finally, the key targets for predictive mechanisms were experimentally verified.Results: The epileptic model was successfully established, and BA had anti-epileptic effects. Epileptic rats displayed significant cognitive dysfunction, and BA markedly ameliorated cognitive dysfunction. Further, we also discovered that BA treatment mitigated neurodegeneration of the hippocampus CA3 regions, thereby ameliorated cognitive dysfunction of epileptic rats. Subsequent network pharmacology analysis was implemented to reveal a possible mechanism of BA in the anti-epileptic process and the TLR4/MYD88/Caspase-3 pathway was predicted. Finally, experimental studies showed that BA exerted an anti-epileptic effect by activating the TLR4/MYD88/Caspase-3 pathway in PTZ-induced epileptic rats.Conclusion: In conclusion, BA had a protective effect against PTZ-induced seizures. BA improved cognitive dysfunction and exerted a neuroprotective action. The anti-epileptic effects of BA may be potentially through activation of the TLR4/MYD88/Caspase-3 pathway.Keywords: baicalin, pentylenetetrazol, epilepsy, cognitive dysfunction, network pharmacology, TLR4/MYD88/Caspase-3